1991
DOI: 10.1093/geront/31.5.666
|View full text |Cite
|
Sign up to set email alerts
|

Travel Behavior of Nursing Home Residents Perceived as Wanderers and Nonwanderers

Abstract: A video-based observational methodology was used to assess the travel behaviors of 40 nursing home residents, 24 of whom were identified by nursing staff as wanderers. Travel was monitored continuously for 30 days, resulting in the recording of over 5,000 unassisted travel events. Four basic travel patterns were observed: direct travel (86.8%), lapping (11.6%), random travel (.9%), and pacing (.7%). Travel efficiency (percentage of direct travel) was significantly related to cognitive status (r = .56), with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1
9

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(130 citation statements)
references
References 0 publications
3
117
1
9
Order By: Relevance
“…Martino-Salzman and colleagues 7 reported that, in an observational study of 40 residents, the frequency of wandering peaked around 7 p.m. Lapping was the wandering pattern in 90% of the cases and random walking represented 5% of wandering.…”
Section: The Wandering Cyclementioning
confidence: 96%
See 2 more Smart Citations
“…Martino-Salzman and colleagues 7 reported that, in an observational study of 40 residents, the frequency of wandering peaked around 7 p.m. Lapping was the wandering pattern in 90% of the cases and random walking represented 5% of wandering.…”
Section: The Wandering Cyclementioning
confidence: 96%
“…Random and lapping patterns of wandering increased as a percentage of overall ambulation as cognitive function declined, while the pacing pattern remains stable through all levels of impairment. 7 Also Algase and colleagues 138 reported that severely impaired patients ambulate more. However, it has been highlighted that although wandering behaviour (as other behavioural symptoms) becomes more common as cognitive impairment increases, the relationship is not linear but can be represented by a concave function.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent advances in measuring wandering, at least in long-term care settings, have demonstrated that it has various geographical patterns (random, lapping, and pacing) and a multidimensional structure [1,[10][11][12][13]. These patterns and dimensions now provide a more elaborate means for investigating wandering in relation to possible explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Wandering behaviors have been classified as random walking (ambulation having frequent direction changes), lapping (moving in circuitous or looping fashion), pacing (moving back and forth repetitively between two points) and direct ambulation [6]. Random wandering becomes more prevalent with increased cognitive impairment while pacing is less frequent, is not significantly associated with cognitive impairment, and might be more an indication of agitation or anxiety.…”
Section: Characterizing Wandering Behaviorsmentioning
confidence: 99%